Faktor yang mempengaruhi Literasi Sains Siswa SMP: Studi Empiris - Ade Mayasari; Usmeldi (Postgraduate, University of Mataram, 2023)
This research goals to find out the effect of factors that affecting Junior High School scientific literacy such as reading habit, learning motivation, learning achievement, parental attention and creativity, and the effect between each variable. This empirical study used the PLS-SEM in data analysis with SmartPLS 3.0 version app. The number of study samples was 270 students. The samples were taken by probability sampling technique with stratified random sampling type by school accreditation. Questionnaire and test techniques were employed in data collection. The output revealed that there were significant effect of reading habit and creativity on scientific literacy, with a t-value â‰¥ t-statistic of 1.96. There was no significant effect of learning motivation, learning achievement and parental attention on scientific literacy, with a t-value â‰¤ t-statistic of 1.96. In addition, there were significant effect of reading habit on learning motivation and creativity, parental attention to reading habit, learning motivation and learning achievement, and learning motivation to learning achievement and creativity.